State of The Art Ilmu Administrasi Negara - Moeljarto Tjokrowinoto (Jurnal Ilmu Sosial dan Ilmu Politik, 2002)
The study of Public Adminitstration has been shifting, both in terms of its substance and its approach/methodology. The shifting has been driven by the dissatisfaction to empirical/positivistic approach which, in fact, took place within the entire body of social science. Within the light of such dissatisfaction, the scholars of public administration increasingly more sensitive to contextual aspect of public administration. Their interest also becoming more focused of the issue of policy-making. These two aspect eventually brougt about the birth of new public administration.